Efficacy of commercially available insecticides against yellow stem borer (Scirpophaga incertulas Walker.) - Katel, Shambhu; Timsina, Sandipa; Adhikari, Nirmal (Future Science, 2023)
Field research was conducted in PMAMP, (PIU) Jhapa, Nepal, Rice Zone against Yellow Stem Borer by using different chemical insecticides commercially available in Nepal to test their efficacy. The research was done in Randomized Completely Block Design (RCBD) with three replication, and seven treatment i.e., 6 chemical treatment namely Cartap hydrochloride 75SC, Thiamethoxan 25WB, Acetamiprid 20 SP, Chlorpyriphos 20 EC, Quinalphas 25 EC and Lambda Cyhalothrin 5 EC and one control for five months. It is concluded that Chlorpyriphos 20 EC is most effective in reducing the infestation rate of dead heart and white head. Similarly, the highest yield was observed in Chlorpyriphos 20 EC with 5.563 ton ha-1.